IT Systems Supporting Finance and Accounting - Wyslocka, E. (Электронное моделирование, 2009)
The paper contains a description of IT needs of mid-sized companies in the area of financial and accounting software. Activities undertaken on particular stages of acquiring new IT system and associated problems and the most relevant requirements, which should be met by financial and accounting software used to keep the books of accounts, were also discussed. These requirements are strictly defined in the Accounting Act, however a transcription on the IT language and adjustment of created software reveal many unexpected problems. The most common difficulties are discussed in this paper. Описаны информационные технологии (ИТ), необходимые для финансового и бухгалтерского программного обеспечения компаний среднего размера. Описаны мероприятия, проводимые на определенных этапах приобретения новых систем ИТ, и сопутствующие проблемы. Проанализированы наиболее важные требования к программному обеспечению финансового и бухгалтерского учета. Эти требования определены в «Законе о бухгалтерском учете», однако при их записи на языке ИТ и адаптации к созданному программному обеспечению обнаруживается много неожиданных проблем. Рассмотрены наиболее общие из них. Описано інформаційні технології (ІТ), необхідні для фінансового та бухгалтерского програмного забезпечення компаній середнього розміру. Описано заходи, що проводяться на визначених етапах придбання нових систем ІТ, а також супутні проблеми. Проаналізовано найважливіші вимоги до програмного забезпечення фінансового та бухгалтерского обліку. Ці вимоги визначено у «Законі про бухгалтерський облік», однак при їх записуванні мовою ІТ і адаптації до створеного програмного забезпечення виявляється багато неочікуваних проблем. Розглянуто найзагальнійші з них.